GsMTx4 reduces the pressor response during dynamic hindlimb skeletal muscle stretch in decerebrate rats - Sanderson, Bailey (Kansas State University, 2018)
Mechanical signals within contracting skeletal muscles contribute to the generation of the exercise pressor reflex; an important autonomic and cardiovascular control mechanism. In decerebrate rats, GsMTx4, a mechanically–activated channel inhibitor that is partially selective for piezo channels, was found recently to reduce the pressor response during static hindlimb muscle stretch; a maneuver used to investigate the mechanical component of the exercise pressor reflex (i.e., the mechanoreflex). However, the effect was found only during the very initial phase of the stretch when muscle length was changing which may have reflected the inhibition of rapidly-deactivating piezo 2 channels and the fact that different mechanically-activated channels with slower deactivation kinetics evoked the pressor response during the static phase of the maneuver. We tested the hypothesis that in decerebrate, unanesthetized rats, GsMTx4 would reduce the pressor response throughout the duration of a 30 second, 1 Hz dynamic hindlimb muscle stretch protocol. We found that the injection of 10 µg of GsMTx4 into the arterial supply of a hindlimb reduced the peak pressor response (control: 15±4, GsMTx4: 5±2 mmHg, p<0.05, n=8) and the pressor response at multiple time points throughout the duration of the stretch. GsMTx4, however, had no effect on the pressor response to the hindlimb arterial injection of lactic acid. Moreover, the injection of GsMTx4 into the jugular vein (a systemic control, n=5) or the injection of saline into the hindlimb arterial supply (a vehicle control, n=4) had no effect on the pressor response during dynamic stretch. We conclude that GsMTx4 reduced the pressor response throughout the duration of a 1 Hz dynamic stretch protocol which may have reflected the inhibition of piezo 2 channels throughout the dynamic stretch maneuver.
Keywords: piezo channels; exercise pressor reflex; mechanoreflex; blood pressure